Opportunities of Using Information and Communication Technology in Reducing Poverty (Universitas Negeri Semarang, 2020)
The development of Information and Communication Technology (ICT) is believed to improve the quality of human life, reduce inequality, and encourage the acceleration of poverty reduction. ICT can be developed as an alternative poverty alleviation program. The purpose of this study was to determine the opportunities of utilization of ICT in reducing poverty in Sumedang Regency and Bandung City. This study used quantitative methods with sources taken from National Socio-Economic Survey (Susenas) data in 2018. The data was analyzed by the Probit Regression method. ICT variables consisted of the ownership of cellular phones, computer use, and internet access. The results of the econometric model indicate that ICT can reduce the likelihood of poverty after being controlled by other related variables such as age, gender, education level, number of household members, access to business credit, and employment status. The government is expected to synergize with stakeholders to improve public services integrated with poverty reduction through the use of ICT, educating the public with productive internet, and expanding the development of ICT infrastructure.